KAJIAN TENTANG JALUR PEDESTRIAN BERDASARKAN ASPEK KENYAMANAN - Sirait, Jhon Kalvin M; Naibaho, Polin D.R.; Aritonang, Emmy Ria (Unika Santo Thomas, 2018)
Pedestrian path is a space for pedestrian activities to carry out activities and to provide services topedestrians so that it can improve the smoothness, safety, and comfort of pedestrians when crossing it. Infact the pedestrian paths that exist are mostly unable to meet the passions of pedestrians. The length oftime pedestrians are less noticed, which should be passed comfortably suddenly blocked by poles, trees,trash cans, stops, and traffic signs because the placement is not adjusted to the place so that thecirculation of road users becomes narrow and disturbed. This study aims to find aspects of comfort in thepedestrian path. Research uses quantative methods. This study found that some of the pedestrian path inthe study area were comfortable, but some were uncomfortable.